A Case of Rectal Endometriosis Misdiagnosed as Rectal Malignancy on Three Colonoscopies and Biopsies Sharing a Combined Literature Review - Liang Y; Mei L; Ning Q; Zhang J; Fei J; Dong J (Dove Medical Press, 2024)
Yufei Liang,1 Lina Mei,2 Qipeng Ning,2 Jiao Zhang,2 Jingying Fei,3 Jie Dong1 1Department of Gynaecology and Obstetrics, Huzhou Maternity & Child Health Care Hospital, Huzhou, People's Republic of China; 2Department of Digestive, Huzhou Maternity & Child Health Care Hospital, Huzhou, People's Republic of China; 3Department of Ultrasound, Huzhou Maternity & Child Health Care Hospital, Huzhou, People's Republic of ChinaCorrespondence: Jie Dong, Department of Gynaecology and Obstetrics, Huzhou Maternity & Child Health Care Hospital, No. 2 East Street, Wuxing District, Huzhou City, Zhejiang Province, People's Republic of China, Email 94276941@qq.comBackground: Endometriosis involves the intestine, and its clinical manifestations are nonspecific and lack of etiological manifestations. The diagnosis is difficult, which often leads to misdiagnosis. We report a case of endometriosis which was misdiagnosed as intestinal malignant tumor after colonoscopy and three biopsies.Case Presentation: We reported a 42-year-old woman who went to see a doctor because of anal distension. She was examined by three gastrointestinal endoscopists at different levels in different hospitals and underwent biopsy at the same time. Combined with clinical manifestations, imaging examination, endoscopic examination and pathological examination, she was misdiagnosed as intestinal malignant tumor, and partial intestinal resection was performed according to the surgical principle of malignant tumor.Conclusion: Although there are advanced gastrointestinal endoscopy and imaging techniques, intestinal endometriosis is still easy to be misdiagnosed. As our case report shows, after three colonoscopy and biopsy, it is still misdiagnosed as intestinal malignant tumor. Further research is needed to improve the ability of preoperative diagnosis, which deserves the attention of gastroenterologists and obstetricians and gynecologists.Keywords: endometriosis, intestinal malignant tumor, colonoscopy